Quantitative late gadolinium enhancement cardiac magnetic resonance analysis of the relationship between ablation parameter and left atrial tissue lesion following pulmonary vein isolation - Wang, Qian; Huang, Bingyu; Huo, Shengqi; Guo, Junyi; Li, Haojie; Jiang, Tao; Peng, Dewei; Men, Lintong; Tang, Dazhong; Xiang, Chunlin; Luo, Yi; Pi, Xiu; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: The impact of ablation parameters on acute tissue lesion formation after pulmonary vein isolation (PVI) has not been sufficiently evaluated in patients with atrial fibrillation. Radiofrequency ablation lesion can be visualized by late gadolinium enhancement cardiac magnetic resonance (LGE-CMR). We sought to quantitatively analyze the relationship between ablation parameter and tissue lesion following PVI at different segments of pulmonary vein (PV) using LGE-CMR. Methods: Twenty-one patients with atrial fibrillation who underwent PVI procedure were retrospectively enrolled. All patients underwent LGE-CMR examination within 3 days after radiofrequency ablation. Ablation parameters during PVI were documented, including lesion size index (LSI), force–time integral (FTI), power, contact force, temperature and time of duration. The ablation point was projected onto 3-dimensional (3D) left atrial shell constructed base on LGE-CMR and corresponding image intensity ratio (IIR) was calculated on the same shell. A tissue lesion point was defined when the LGE-CMR IIR was > 1.2. Results: In total, 1759 ablation points were analyzed. The ablation parameters and IIRs for each PV segment were significantly different (P < 0.0001). IIRs corresponding to ablation points at posterior of PV tended to be higher than those at non-posterior of PV when similar ablation parameters were applied during ablation. LSI was a better predictor of tissue lesion existence following PVI than FTI, contact force, power, temperature, and duration time at non-posterior wall of PV. The IIR showed positive correlation with LSI at non-posterior wall of PV (non-posterior of right PV, r = 0.13, P = 0.001, non-posterior of left PV, r = 0.26, P < 0.0001). Conclusions: When similar ablation parameters were applied during PVI, the posterior wall of PV had more severe tissue lesion than non-posterior wall of PV. Therefore, it was reasonable to decrease ablation energy at posterior wall of PV. Moreover, LSI was a better index to reflect tissue lesion quality following PVI at non-posterior of PV.